Effects of four anaesthetic protocols on the neurological and cardiorespiratory variables of puppies born by caesarean section - Luna, Stélio Pacca Loureiro [UNESP]; Cassu, R. N. [UNESP]; Castro, G. B. [UNESP]; Teixeira Neto, Francisco José [UNESP]; Silvia Júnior, J. R. [UNESP]; Lopes, Maria Denise [UNESP] (British Veterinary Assoc, 2004)
Twenty-four bitches which had been in labour for less than 12 hours were randomly divided into four groups of six. They all received 0(.)5 mg/kg of chlorpromazine intravenously as premedication, followed 15 minutes later by either 8 mg/kg of thiopentone intravenously (group 1), 2 mg/kg of ketamine and 0-5 mg/kg of midazolam intravenously (group 2), 5 mg/kg of propofol intravenously (group 3), or 2(.)5 mg/kg of 2 per cent lidocaine with adrenaline and 0(.)625 mg/kg of 0(.)5 per cent bupivacaine with adrenaline epidurally (group 4). Except for group 4, the bitches were intubated and anaesthesia was maintained with enflurane. The puppies' heart and respiratory rates and their pain, sucking, anogenital, magnum and flexion reflexes were measured as they were removed from the uterus. The puppies' respiratory rate was higher after epidural anaesthesia. in general the puppies' neurological reflexes were most depressed after midazolam/ketamine, followed by thiopentone, propofol and epidural anaesthesia.
Keywords: Adrenalin; Anesthetic agent; Bupivacaine; Chlorpromazine; Enflurane; Etrane; Ketamine; Lidocaine; Midazolam; Oxygen; Propofol; Thiopental; Animal care; Birth; Breathing rate; Cardiovascular function; Cesarean section; Clinical protocol; Controlled study; Dog; Endotracheal intubation; Epidural anesthesia; Female; Flexor reflex; Genital system; Heart rate; Labor; Measurement; Nervous system function; Nonhuman; Pain; Premedication; Randomization; Respiratory function; Sucking; Uterus; Anesthesia, Inhalation; Anesthesia, Intravenous; Anesthetics, Combined; Animals; Bupivacaine; Cesarean Section; Chlorpromazine; Dogs; Enflurane; Epinephrine; Female; Heart Rate; Ketamine; Lidocaine; Midazolam; Pregnancy; Propofol; Random Allocation; Reflex; Respiration; Thiopental; Animalia; Canidae; Canis familiaris